Republic of Palau : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that the Republic of Palau faces a number of development challenges. Substantial improvements in human and physical infrastructure are needed to sustain higher growth rates. About 80 percent of the land area is on the Babeldaob Island, which is virtually inaccessible now, but it is expected to develop rapidly after the completion of a Japan-funded bridge in 2002 and a United States-funded island access road in 2004. Asset balances have been declining as a result of drawdowns to finance fiscal deficits, as well as recent investment losses.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet